Measurement and thermodynamic modeling of ternary (liquid + liquid) equilibria for extraction of 2, 3-butanediol from aqueous solution with different solvents at T = 298.2 K, T = 308.2 K, and T = 318.2 K. Issue 5 (4th May 2022) - Wu, Yanyang; Chen, Weipeng; Li, Renlong; Wu, Bin; Ji, Lijun; Chen, Kui
Abstract: Liquid − liquid equilibrium (LLE) data for the water + 2, 3-butanediol (2, 3-BD) + solvent (n-hexanol or iso-pentanol) ternary systems were obtained at different temperatures (298.2, 308.2, and 318.2 K) under 101.3 kPa. Distribution coefficients and separation factors were calculated accordingly. Distribution coefficients and separation factors were greater than 0.2 and 2.5, respectively, for both n-hexanol and iso-pentanol, which indicated that they were feasible to extract 2, 3-BD from aqueous solution. Meanwhile, the reliability of the experimental LLE data was confirmed by both Othmer − Tobias equation and Hand equation. Lastly, the LLE data were correlated by both thermodynamic nonrandom two-liquid (NRTL) and universal quasi-chemical (UNIQUAC) models, and their binary interaction parameters were correlated from the data. In addition, topological analysis related to the Gibbs minor common tangent test was applied to validate the binary interaction parameters. Supplemental data for this article is available online at here.